Assessing the Consequences of External Reference Pricing for Global Access to Medicines and Innovation: Economic Analysis and Policy Implications - Incze, András; Kaló, Zoltán; Espín, Jaime; Kiss, Éva; Kessabi, Sophia; Garrison, Louis P. (Frontiers in Pharmacology, 2022)
Background: External reference pricing (ERP) is used to set pharmaceutical prices to improve affordability, but its application may have negative consequences on patient access—thus, equity—across countries and on global innovation. With the US contemplating ERP, negative effects could be magnified. Our aim: identify and quantify some major consequences of ERP. Research design, methods: Besides relying on databases and ERP modelling, we developed a heart failure case study. 4-step approach: (1) review ERP policies; (2) establish worldwide “price corridor”; (3) quantify patient access and health outcomes impact by ERP; (4) estimate ERP impact on innovation. Results: Our ERP referencing analysis highlights its perverse effects especially in lower-income countries. As counterstrategies to protect their revenues, manufacturers often implement tight list price corridors or launch avoidance/delays. Consequences include suboptimal patient access— hence, worse outcomes—illustrated by our case study: 500,000+ QALYs health loss. Additionally, the ensuing revenue reduction would likely cause innovation loss by one additional medicine that would have benefitted future patients. Conclusion: This research provides key insights on potential unintentional consequences of medicine price setting by ERP worldwide and under a new proposal for the US. Our results can inform stakeholder discussions to improve patient access to innovative medicines globally.